The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/jae/ejv016
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Structural Change to Productivity Growth: Evidence from Tunisia

Abstract: The objective of this paper is to analyze the evolution of productivity and the contribution of structural change to productivity growth in Tunisia since the mid eighties. Using sectoral and firm data we show that productivity increased at a relatively interesting pace, but that the contribution of structural change remained very limited. Trade and labor market reforms did not seem to increase it. The main reasons are barriers to entry in some sectors, the inefficiency of factor markets, and the focus of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
0
21
2
Order By: Relevance
“…The other variable is foreign investment. Chen et al (2011) showed foreign investment has a significant positive effect on labour productivity growth but Marouani and Mouelhi (2016) showed that it is not significant. Likewise with the education level variable in the research of Marouani and Mouelhi (2016) that supported structural bonus, education does not significantly influence productivity growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The other variable is foreign investment. Chen et al (2011) showed foreign investment has a significant positive effect on labour productivity growth but Marouani and Mouelhi (2016) showed that it is not significant. Likewise with the education level variable in the research of Marouani and Mouelhi (2016) that supported structural bonus, education does not significantly influence productivity growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al (2011) showed foreign investment has a significant positive effect on labour productivity growth but Marouani and Mouelhi (2016) showed that it is not significant. Likewise with the education level variable in the research of Marouani and Mouelhi (2016) that supported structural bonus, education does not significantly influence productivity growth. However, in the study of Fagerberg (2000) which showed a structural burden, this variable has a significant positive impact, where higher education attainment increases labour productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This small gap was attributed to low productivity in the manufacturing sector, which is mostly dependent on simple assembly activities (World Bank 2014). Marouani and Mouelhi (2016) show that productivity in Tunisia increased at a relatively sustained pace in the past three decades. Also, productivity growth was mainly within sectors, suggesting no structural change (Marouani and Mouelhi 2016).…”
Section: Structural Change In Agriculturementioning
confidence: 96%
“…Marouani and Mouelhi (2016) show that productivity in Tunisia increased at a relatively sustained pace in the past three decades. Also, productivity growth was mainly within sectors, suggesting no structural change (Marouani and Mouelhi 2016). Moreover, high-productivity sectors, such as communications, did not witness an increase in labor share.…”
Section: Structural Change In Agriculturementioning
confidence: 96%